CHERRY EYE REPOSITION IN FRENCH BULLDOG DOGS WITH THE MORGAN POCKET METHOD - Kusuma, I Made Gede Wijaya; Wirata, I Wayan; Wandia, I Nengah (Buletin Veteriner Udayana, 2024)
The eye has three eyelids, including the upper eyelid, the lower eyelid and the third eyelid. Cherry Eye is a condition where the nictitating glands protrude from their normal position due to weak connective tissue attachment, so that the nictitating membrane looks swollen and protrudes like a cherry. The aim of writing this article is to add information about how to treat cherry eye cases using the Morgan pocket surgery method in dogs. A French bulldog named Piko, 3 years old, male, weighing 12 kg, has black and brown hair, has a protrusion in his left eye. Physical examination is carried out by inspection, palpation, and auscultation. Routine hematology examinations are performed to determine the physiological condition of the case dogs. The case of the dog was treated by performing surgery to reposition the lump on the eye using the Morgan Pocket method. Based on the anamnesis and results of clinical examination of the case dog, a diagnosis of follicular ophthalmitis (cherry eye) was obtained in the left eye. The treatment procedure used is the Morgan pocket method, which is surgery to reposition the nictitating membrane by creating a pocket. Treatment of follicular ophthalmitis (cherry eye) must be done immediately, so as not to cause secondary infections which will worsen the condition of the dog's eyes.